UMP obtains KPT CAP Penjana Grant to assist graduates - Siti Nurfarmy, Ibrahim (2021)
KUANTAN, 8 October 2021 – Universiti Malaysia Pahang (UMP), through the Centre of Alumni Relations and Graduate Employability, has successfully obtained the KPT-Career Advancement Programme (CAP)@State Penjana grant amounting to RM2,587,200.